2007
DOI: 10.1103/physrevlett.98.105701
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Structural Transitions: Circumventing the Broken-Ergodicity Problem

Abstract: We consider systems undergoing very-low-temperature solid-solid transitions, exhibiting the well-known "broken-ergodicity" problem that is often so severe that even the replica exchange method converges too slowly. We propose an improvement of the latter, which consists of coupling the lower-temperature random walks to analytically generated random walks corresponding to an auxiliary harmonic superposition system. Numerically accurate results are obtained for several Lennard-Jones clusters, which have so far b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 19 publications
1
100
0
Order By: Relevance
“…It is important to emphasize that caution must always be exercised when dealing with sparse distributions. As discussed elsewhere, 22 for example, tempering methods alone may be inadequate for the treatment of systems that exhibit lowtemperature, solid-solid transitions. The CEI method presented here is thus intended as a way to improve the efficiency of tempering approaches in situations where they are appropriate, as opposed to a means for extending their intrinsic applicability.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that caution must always be exercised when dealing with sparse distributions. As discussed elsewhere, 22 for example, tempering methods alone may be inadequate for the treatment of systems that exhibit lowtemperature, solid-solid transitions. The CEI method presented here is thus intended as a way to improve the efficiency of tempering approaches in situations where they are appropriate, as opposed to a means for extending their intrinsic applicability.…”
Section: Discussionmentioning
confidence: 99%
“…10 Due to the double-funneled energy landscape of LJ 31 , associated with the Mackay→ anti-Mackay transition, the heat capacity displays a narrow peak around T Ϸ 0.027 besides a core melting peak around T Ϸ 0.32. This solid-solid transition is very sensitive to the convergence of simulations, 11,12,23,55 which makes LJ 31 a good benchmark for newly developed sampling algorithms in a rugged energy landscape. A recent study 12 reported that a single replica enhanced sampling employing the Wang-Landau 56 or the multicanonical algorithm 29 failed to capture a correct thermodynamics of the solid-solid transition.…”
Section: Applications: Lj 31 Atom Clustersmentioning
confidence: 99%
“…This approach to binding free energy calculations is employed in the mining minima algorithm, 35 which has been successfully applied to various biomacromolecular systems, especially small host-guest systems. Benchmark superposition calculations for atomic and molecular clusters show that the energy landscape approach can be much faster than MD or MC based methods, especially for cases of broken ergodicity, 36,37,[37][38][39] since the superposition partition function is explicitly ergodic.…”
Section: Introductionmentioning
confidence: 99%